Organoids in the oral and maxillofacial region: present and future - Yufei Wu; Xiang Li; Hanzhe Liu; Xiao Yang; Rui Li; Hui Zhao; Zhengjun Shang (Nature Publishing Group, 2024)
Abstract The oral and maxillofacial region comprises a variety of organs made up of multiple soft and hard tissue, which are anatomically vulnerable to the pathogenic factors of trauma, inflammation, and cancer. The studies of this intricate entity have been long-termly challenged by a lack of versatile preclinical models. Recently, the advancements in the organoid industry have provided novel strategies to break through this dilemma. Here, we summarize the existing biological and engineering approaches that were employed to generate oral and maxillofacial organoids. Then, we detail the use of modified co-culture methods, such as cell cluster co-inoculation and air-liquid interface culture technology to reconstitute the vascular network and immune microenvironment in assembled organoids. We further retrospect the existing oral and maxillofacial assembled organoids and their potential to recapitulate the homeostasis in parental tissues such as tooth, salivary gland, and mucosa. Finally, we discuss how the next-generation organoids may benefit to regenerative and precision medicine for treatment of oral-maxillofacial illness.